Promoting Sustainable Marine Ecotourism: The Role of e-WOM, Environmental Attitude, and UTAUT Model in Supporting Blue Economy in Indonesia - Antonius Satria Hadi; Utami Tunjung Sari; Tirsa Trisandi Matipa; Niken Permata Sari (Integrated Journal of Business and Economics (IJBE), 2026)
The objective of this study is to analyze the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, and environmental attitude on marine ecotourism behavior, with e-WOM intention and marine ecotourism intention serving as mediating variables. A quantitative approach was employed using path analysis through the SmartPLS 4 application, based on data collected from 248 tourist respondents who had visited marine ecotourism destinations. The study proposed nine hypotheses, of which two were rejected. The findings indicate that most exogenous constructs significantly affect marine ecotourism behavior, either directly or indirectly. E-WOM intention was identified as a strong mediator, linking perceptions of usefulness, ease of use, and environmental attitudes to sustainable behavior. Additionally, the intention to participate in marine ecotourism plays a crucial role in bridging the influence of several constructs on actual behavioral outcomes. These results underscore the importance of digital communication and personal intention in shaping environmentally responsible tourism behavior. This study contributes theoretically to the development of sustainable tourist behavior models and offers practical implications for destination managers and policymakers in promoting sustainable marine ecotourism in Indonesia.